Prevalence of metabolic syndrome among ethnic groups in China - Xuzhen Qin; Ling Qiu; Guodong Tang; Man-Fung Tsoi; Tao Xu; Lin Zhang; Zhihong Qi; Guangjin Zhu; Bernard M. Y. Cheung (BMC, 2020)
Abstract Background Metabolic syndrome (MetS) is common in China, which has a multi-ethnic population of 1·3 billion. We set out to determine the prevalence of MetS and its components in different ethnic groups. Methods This nationwide cross-sectional survey involved 24,796 participants from eight ethnicities in six provinces in China from 2008 to 2011. MetS was defined using the modified National Cholesterol Education Program Adult Treatment Panel III criteria. Results were analysed using SPSS version 22·0 in 2018. Logistic regression was used for deriving odds ratios and 95% confidence intervals of risk factors for the MetS. Results The prevalence of MetS increased with age from 3·60% to 21·68%. After age standardization, the prevalence of MetS, in descending order, was 35·42% (Korean), 22·82% (Hui), 19·80% (Han), 13·72% (Miao), 12·90% (Tujia), 12·04% (Li), 11·61% (Mongolian), 6·17% (Tibetan). Korean ethnicity was associated with a higher prevalence in five components of MetS, while Tibetan ethnicity was associated with lower prevalence except decreased HDL cholesterol. Logistic regression analyses showed that age, drinking and being non-Tibetan were associated with a higher risk of MetS. Conclusions Within one country, albeit a large one, the prevalence of MetS can vary greatly. Chinese of Korean ethnicity had a much higher prevalence than Tibetan ethnicity. Measures to tackle MetS should be tailored to the ethnic groups within a population.